TNF and its receptors in the CNS: The essential, the desirable and the deleterious effects. (27th August 2015) - Probert, L.
Highlights: TNF signals essential, desirable, and deleterious effects in the CNS depending on normal or diseased conditions. Functional multiplicity of TNF results from a two-ligand, two-receptor system and differential regulation on CNS cell types. Targeting soluble TNF and TNFR1 is a potential new therapeutic strategy for multiple sclerosis and neurodegeneration. Abstract: Tumor necrosis factor (TNF) is the prototypic pro-inflammatory cytokine. It is central to host defense and inflammatory responses but under certain circumstances also triggers cell death and tissue degeneration. Its pleiotropic effects often lead to opposing outcomes during the development of immune-mediated diseases, particularly those affecting the central nervous system (CNS). The reported contradictions may result from lack of precision in discussing TNF. TNF signaling comprises at minimum a two-ligand (soluble and transmembrane TNF) and two-receptor (TNFR1 and TNFR2) system, with ligands and receptors both differentially expressed and regulated on different cell types. The "functional multiplicity" this engenders is the focus of much research, but there is still no general consensus on functional outcomes of TNF signaling in general, let alone in the CNS. In this review, evidence showing the effects of TNF in the CNS under physiological and pathophysiological conditions is placed in the context of major advances in understanding of the cellular and molecular mechanisms that govern TNF function in general. Thus the roles of TNF signaling in the CNS shift from the conventional dichotomy of beneficial and deleterious, that mainly explain effects under pathological conditions, to incorporate a growing number of "essential" and "desirable" roles for TNF and its main cellular source in the CNS, microglia, under physiological conditions including regulation of neuronal activity and maintenance of myelin. An improved holistic view of TNF function in the CNS might better reconcile the expansive experimental data with stark clinical evidence that reduced functioning of TNF and its dominant pro-inflammatory receptor, TNFR1, are risk factors for the development of multiple sclerosis. It will also facilitate the safe translation of basic research findings from animal models to humans and propel the development of more selective anti-TNF therapies aimed at selectively inhibiting deleterious effects of this cytokine while maintaining its essential and desirable ones, in the periphery and the CNS.